1945
DOI: 10.1111/j.1748-1716.1945.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Lymphocyte Production. Investigations on the Nucleic Acid Turnover in the Lymphoid Organs

Abstract: Summary. The importance of the various lymphoid organs as a source of blood lymphocytes is studied by determinations of the rate of desoxyribose nucleic acid formation in the organs under examination. The rate of formation of nucleic acid is estimated by means of the radioactive indicator method. The animal material is normal albino rats in different age groups. A large nucleic acid turnover is observed in the lymphoid organs. The greatest renewal takes place in the thymus, the rate of renewal in mature animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1947
1947
2008
2008

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The experiments with tritiated thymidine showed that a very small proportion of the cells in the thoracic duct were newly formed and that no store of new small lymphocytes remained in the lymph nodes. Similarly, the daily production of new lymphocytes, as calculated from mitotic counts (Kindred, 1942) and from DNA turnover (Andreasen & Ottesen, 1945) in the intestinal lymphoid tissue of rats, amounts at the most to about 1/10 of the actual output from the thoracic duct as determined by the technique of Bollman et al (1948) (author's calculation). This fraction is an upper limit, for the assumption that mitotic counts and DNA turnover are measures of new lymphocyte production requires independent proof; many cells may be produced and die within the lymph nodes without ever leaving them.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments with tritiated thymidine showed that a very small proportion of the cells in the thoracic duct were newly formed and that no store of new small lymphocytes remained in the lymph nodes. Similarly, the daily production of new lymphocytes, as calculated from mitotic counts (Kindred, 1942) and from DNA turnover (Andreasen & Ottesen, 1945) in the intestinal lymphoid tissue of rats, amounts at the most to about 1/10 of the actual output from the thoracic duct as determined by the technique of Bollman et al (1948) (author's calculation). This fraction is an upper limit, for the assumption that mitotic counts and DNA turnover are measures of new lymphocyte production requires independent proof; many cells may be produced and die within the lymph nodes without ever leaving them.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that dividing or secreting cells may be more permeable to phosphate than others (1). Bone marrow DNA showed a very high specific activity and that for the thymus decreased with increasing age of the animal (24). The rate of p82 incorporation in DNA reported by Brues et al (25) was much higher that that found by Hevesy and Ottesen (20) but was probably contaminated with RNA.…”
Section: Nucleic Acids and Nucleoproteinsmentioning
confidence: 67%
“…Ultra-violet and phase contrast microscopy have failed to differentiate between lymphocytes from the various sites. There is substantial evidence in the literature to corroborate these findings [Kindred, 1942;Andreasen and Ottesen, 1945;Andreasen and Christensen, 1949;Osogoe and Hitachi, 1950;Yoffey, 1941 andFichtelius, 1953].…”
Section: Discussionmentioning
confidence: 92%